Analysis of postural changes on lumbar spine of pregnant women - Afonso, Max dos Santos (2019)
This study aimed to analyze the postural change in lumbar spine of pregnant women through photogrammetry in the three trimesters of pregnancy and check the frequency of low back pain. This is a quantitative study, consisting of 21 pregnant women, carried out from September to November 2012, using questionnaires on the profile of the population, the Nordic Musculoskeletal Questionnaire and the International Physical Activity Questionnaire. Palpation and location of anatomical points were made for placing markers. After that, pregnant women were subjected to the photographic record and the angles analyzed using the Postural Assessment Software. A high index of pain in the lumbar region of pregnant women was found for a total of 72%, with all showing an increase in lumbar lordosis. Significant postural changes among the three trimesters of pregnancy were verified and the presence of low back pain was reported by the majority of pregnant women.